Modelling of Tractor Fuel Consumption for Harrowing Operation in a Sandy Loam Soil - Oyelade, O. A.; Oni, K. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
In the study of agricultural machinery management, fuel consumption is considered as a very important factor that plays a significant role in the selection and management of tractors and equipment. In Nigeria, there are no tractor fuel consumption models developed for harrowing operation. Considering the importance of harrowing operation to tillage practice in Nigerian agriculture, it became necessary to embark on the study on the modelling of tractor fuel consumption in litres per hectare (L/ha) during harrowing operation in a sandy loam soil using available information gathered from the National Centre for Agricultural Mechanization (NCAM) Tractor Test Reports. A multiple linear regression method was used to develop the model. A 10-repeated 10-fold cross-validation method was used to validate the model. The study revealed that the model developed for harrowing operation had a R2-value of 0.477 showing tractor power rating as the only operation parameter contributing to the model developed. Cross-validation revealed that the harrowing operation model had a test error value of 0.986 L/ha. The study also identified other contributing factors to tractor fuel consumption during harrowing operation in a sandy loam soil. The model developed for tractor fuel consumption during harrowing operation in a sandy loam soil is recommended for use in budgeting for diesel consumption.